Successful Treatment of a Fibromyalgia Patient Using a Homeopathic Preparation of Cannabis sativa - Carvalho, Jozélio Freire de; Ribeiro, Maria Fernanda Leal dos Santos (Homeopathy, 2023)
Background Homeopathy has been used in observational and controlled studies to treat patients with fibromyalgia (FM), but none has previously used the remedy Cannabis sativa.Case History A 51-year-old female patient presenting with diffuse pain and sleep disorder was diagnosed with FM using the relevant American College of Rheumatology criteria. She reported having 18 tender points, a pain score (visual analog scale, VAS) of 9.0, and a well-being VAS of 5.0. She was prescribed Cannabis sativa 6 cH, five drops sublingually thrice a day.Results After 2 months, she returned asymptomatic, with 0 tender points, pain VAS of 0, and well-being VAS of 9.0. The Modified Naranjo Criteria for Homeopathy score was equal to +9, suggesting the clinical outcome was causally attributable to the medicine prescribed.Conclusion This case study reveals the positive role of homeopathic treatment in FM. Studies using a randomized controlled design, including pragmatic trials to determine treatment effectiveness in real-world clinical practice, are indicated in this field.
Keywords: cannabis; fibromyalgia; chronic condition; homeopathy